2014
DOI: 10.1590/s0044-59672014000100013
|View full text |Cite
|
Sign up to set email alerts
|

Histologia e histoquímica do tubo digestório de Phrynops geoffroanus (Testudines, Chelidae)

Abstract: . Juiz de Fora, Minas Gerais, Brasil. bernadete.sousa@ufjf.edu.br. RESUMOPhrynops geoffroanus é o quelônio onívoro com mais ampla distribuição geográfica na América do Sul. Este trabalho descreve a histologia e histoquímica do tubo digestório desta espécie, relacionando as características dos órgãos com seu hábito alimentar. O esôfago, estômago e intestino de quatro espécimes foram fixados em formol 10% e incluídos em parafina por técnica histológica de rotina. Depois, cortes de 5 μm de espessura foram corados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the ileum, we had an increase in PAS+AB+ goblet cells. This result indicates a potential of microbiota maintained by PAS+AB+goblet cell secretion (Frankel et al , 1995 ; Deplancke & Gaskins, 2001 ; Azevedo et al, 2007 ; Vieira-Lopes et al, 2014 ). The difference found in these proportions is related to the treatment, considering the reversal observed after its interruption, but the alteration is not sufficient to cause loss of the small intestine function.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the ileum, we had an increase in PAS+AB+ goblet cells. This result indicates a potential of microbiota maintained by PAS+AB+goblet cell secretion (Frankel et al , 1995 ; Deplancke & Gaskins, 2001 ; Azevedo et al, 2007 ; Vieira-Lopes et al, 2014 ). The difference found in these proportions is related to the treatment, considering the reversal observed after its interruption, but the alteration is not sufficient to cause loss of the small intestine function.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, it serves as a lubricant for the passage of solids and as a barrier to antigens, bacteria and viruses (Shirazi et al , 2000 ; Walker & Talley, 2011 ; Chawla et al , 2013 ; Kim & Khan, 2013 ). The diet and the use of drugs can alter the distribution and frequency of goblet cells and it is related to the maintenance of bacterial translocation and microbiota (Frankel et al , 1995 ; Deplancke & Gaskins, 2001 ; Azevedo et al, 2007 ; Vieira-Lopes et al, 2014 ). The modifications concerning goblet cells were concentrated in the duodenum and ileum and the results are interesting, considering the typical goblet cell type in both regions.…”
Section: Discussionmentioning
confidence: 99%
“…Calais Junior et al (2016), when describing the esophagus morphology of C. mydas , observed the presence of PAS-positive mucus-producing glands located in the gastroesophageal region mucosa. Vieira-Lopes et al (2014) also verified the presence of well-defined glands interspersed in the mucosal epithelium of the esophagus on some freshwater turtles, such as Phrynops geoffroanus , formed by clear cells in a semicircular arrangement, while Magalhães et al (2014) reported the presence of mucus-producing superficial cells throughout the esophagus when studying the morphology of the DT of freshwater turtles belonging to the Podocnemididae family, forming a continuous layer of secretory cells occupying the entire apical region, stained positively with PAS, more intense in the posterior portion. In addition to these mucus-producing cells, the authors also verified the presence of some goblet cells irregularly distributed among the columnar cells in the epithelium but did not observe esophageal glands.…”
Section: Discussionmentioning
confidence: 99%
“…Mucins are likely to be the first molecules that invading pathogens interact with at the cell surface and thus, can limit binding to other glycoproteins and neutralize the pathogen (30)(31)(32)(33). The diet and the use of drugs can alter the distribution and frequency of goblet cells and it is related to the maintenance of bacterial translocation and microbiota (34)(35)(36)(37). The modifications concerning goblet cells were concentrated in the duodenum and ileum and the results are so interesting considering the typical goblet cell type in both regions.…”
Section: Discussionmentioning
confidence: 99%
“…The modifications concerning goblet cells were concentrated in the duodenum and ileum and the results are so interesting considering the typical goblet cell type in both regions. In duodenum the tendency of increase in PAS+ cell during the treatment and a decrease of the same cell after the treatment interruption indicates a potential of bolus hydration, linked to this type of mucin (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%